Radically rethinking agriculture for the 21st century - Fedoroff, N.V.; Battisti, D.S.; Beachy, Roger N.; Cooper, Peter J.M.; Fischhoff, D.A.; Hodges, C.N.; Knauf, V.C.; Lobell, David B.; Mazur, B.J.; David, S.; Reynolds, Matthew P.; Ronald, Pamela C.; et al. (American Association for the Advancement of Science, 2010)
Population growth, arable land and fresh water limits, and climate change have profound implications for the ability of agriculture to meet this century's demands for food, feed, fiber, and fuel while reducing the environmental impact of their production. Success depends on the acceptance and use of contemporary molecular techniques, as well as the increasing development of farming systems that use saline water and integrate nutrient flows.